Neurovisual Manifestations in Children with Mild COVID-19: An Association to Remember. (4th March 2023) - Costagliola, Giorgio; Vallario, Michele Pio; Santangelo, Andrea; Foiadelli, Thomas; Ragone, Maria Cristina; Battini, Roberta; Tinelli, Francesca; Di Cicco, Maria Elisa; Bonuccelli, Alice; Gaeta, Giovanni; Iozzi, Chiara; Peroni, Diego Giampiero; et al.
ABSTRACT: Neurovisual involvement has been reported in a number of patients with severe SARS-CoV-2 disease (COVID-19), mainly among adult patients. In children, such involvement has been reported in rare cases, often in those presenting with severe forms of COVID-19. The aim of this work is to explore the association between mild COVID-19 and neurovisual manifestations. We report the cases of three previously healthy children who developed neurovisual manifestations following mild acute COVID-19, analysing the clinical phenotype, the latency between the onset of acute COVID-19 and neurovisual involvement, and the kinetic of resolution. Our patients developed different clinical patterns, including visual impairment and ophthalmoplegia. In two cases, these clinical features occurred during acute COVID-19, while in the third patient their development was delayed after 10 days from disease onset. Furthermore, the dynamics of resolution were different, with one patient showing remission after 24 hours, the second after 30 days, and the third showing persistence of the strabismus after 2 months of follow-up. The spreading of COVID-19 among the paediatric population will probably lead to an increase of atypical disease forms, including those presenting with neurovisual involvement. Therefore, a better knowledge of the pathogenic and clinical features of these manifestations is warranted.